Economic Analysis of Goat Enterprises in Kathmandu District - Bhatt, Prem Raj; Neupane, Prakriti (International Journal of Social Sciences and Management, 2023)
This study was conducted in Kathmandu district to perform comparative economic analysis of small and commercial goat enterprises. In the study the average annual return from large enterprises was found to be six times greater than that of small enterprises. The average annual fixed cost of small enterprises was found to be one tenth of that of commercial goat enterprises. The total average annual variable cost of small enterprises was found comparatively less than that of commercial enterprises, which is more than five times less. The per unit goat cost for the small enterprises is also twenty-five hundred less than that of commercial enterprises. The gross profit per year of small enterprise was around sixty thousand rupees with 9.5% gross profit margin ratio while in commercial goat enterprises gross profit per year accounted almost 4 lakh with gross profit margin ratio 10.45%. Similarly, the average benefit cost ratios for small and commercial enterprises were found similar i.e. 1.10 and 1.12 but break even points varied widely as 18.36% and 56% respectively. The study concluded that there is no significant difference in production costs and income among small and commercial goat enterprises present in Kathmandu district testing at 5% level of significance. It also reveals positive aspects of small goat enterprises and at the same time suggests low functional efficiency of commercial goat enterprises in Katmandu district.